Ocular Surface Changes Differ Significantly Between Oxaliplatin- and Diabetes-Induced Polyneuropathy - Schicht, Martin; Sisignano, Marco; Farger, Jessica; Wedel, Saskia; Phunchago, Nichapa; Perumal, Natarajan; Manicam, Caroline; Scholich, Klaus; Geisslinger, Gerd; Paulsen, Friedrich; Lütjen-Drecoll, Elke (International Journal of Molecular Sciences, 2025)
Dry eye disease (DED) is often seen in patients with polyneuropathies (PNs), but the relationship between the different forms of PNs and DED is not known. In oxaliplatin (Ox-)-treated mice with PNs, morphological changes in the sciatic nerve (SN), dorsal root ganglia (DRG), trigeminal ganglia (TG), and the ocular tissues involved in tear formation were investigated. In addition, the tear proteomics and the gene expression of related proteins in the ocular surface tissues as well as inflammatory factors were analyzed. There were significant changes in six tear proteins compared to the controls, with respective changes in gene expression in the ocular tissues. Morphologically, there was a decrease in the number of conjunctival goblet cells and changes in the myofibroblasts surrounding the Meibomian glands. The lacrimal gland appeared normal. In the SN, there was a slight decrease in the number of mitochondria without signs of inflammation. In the DRG, 30–50% of the small- and medium-sized neuronal cells had swollen mitochondria. In contrast, the mitochondria of the TG were unremarkable. The changes in the tear film proteins and the ocular tissue morphology involved in tear formation in OPN differed significantly from those previously described in DPN mice, despite a similar mechanical hypersensitivity and similar morphological features of the DRG. In DPN, these changes led to aqueous-deficient dry eye disease, whereas in OPN, they resulted in evaporative DED. Furthermore, in contrast to DPN, the TG in OPN showed no morphological alterations, which indicates differences in the peripheral nerve changes and ocular nerve damage between the two conditions.
CRIS-Team Scopus Importer:2025-03-28
Keywords: dry eye disease (DED); ocular surface; oxaliplatin (Ox); polyneuropathies (PNs); tear film